Clinical implementation of NIPT – technical and biological challenges. Issue 5 (4th May 2015) - Brady, P.; Brison, N.; Van Den Bogaert, K.; de Ravel, T.; Peeters, H.; Van Esch, H.; Devriendt, K.; Legius, E.; Vermeesch, J.R.
Abstract : Non‐invasive prenatal testing (NIPT) for fetal aneuploidy detection is increasingly being offered in the clinical setting. Whereas the majority of tests only report fetal trisomies 21, 18 and 13, genome‐wide analyses have the potential to detect other fetal, as well as maternal, aneuploidies. In this review, we discuss the technical and clinical advantages and challenges associated with genome‐wide cell‐free fetal DNA profiling. Abstract :